Measuring early childhood development: considerations and evidence regarding the Caregiver Reported Early Development Instruments. Issue 1 (13th April 2021) - McCoy, Dana Charles; Seiden, Jonathan; Waldman, Marcus; Fink, Günther
Abstract: Reflecting a burgeoning political interest in supporting young children around the world, global demand for reliable, valid, and scalable assessments of early childhood development (ECD) is on the rise. One of the more popular sets of tools for measuring the ECD of children under age 3 is the Caregiver Reported Early Development Instruments (CREDI), which includes both a long form for research and evaluation and a short form for population‐level monitoring. In this commentary, we describe the goals and limitations of the CREDI, research to support its use as a population‐level ECD instrument, as well as the major gaps in its evidence base. We also discuss how the work of Alderman and colleagues (in this issue) addresses some of these outstanding gaps, highlighting several critical areas for future research.